A Novel Electrochemical Sensor Based on an Environmentally Friendly Synthesis of Magnetic Chitosan Nanocomposite Carbon Paste Electrode for the Determination of Diclofenac to Control Inflammation - Mohamed Abd-Elsabour; Mortaga M. Abou-Krisha; Sayed H. Kenawy; Tarek A. Yousef (Nanomaterials, 2023)
A simple and eco-friendly electrochemical sensor for the anti-inflammatory diclofenac (DIC) was developed in a chitosan nanocomposite carbon paste electrode (M-Chs NC/CPE). The M-Chs NC/CPE was characterized with FTIR, XRD, SEM, and TEM for the size, surface area, and morphology. The produced electrode showed a high electrocatalytic activity to use the DIC in 0.1 M of the BR buffer (pH 3.0). The effect of scanning speed and pH on the DIC oxidation peak suggests that the DIC electrode process has a typical diffusion characteristic with two electrons and two protons. Furthermore, the peak current linearly proportional to the DIC concentration ranged from 0.025 M to 4.0 M with the correlation coefficient (r2). The sensitivity, limit of detection (LOD; 3σ), and the limit of quantification (LOQ; 10σ) were 0.993, 9.6 µA/µM cm2, 0.007 µM, and 0.024 µM, respectively. In the end, the proposed sensor enables the reliable and sensitive detection of DIC in biological and pharmaceutical samples.